Kicking performance in young U9 to U20 soccer players: Assessment of velocity and accuracy simultaneously - Vieira, L. H. P.; Cunha, S. A.; Moraes, R.; Barbieri, F. A.; Aquino, R.; de P. Oliveira, L.; Navarro, M.; Bedo, B. L. S.; Santiago, P. R. P. (Research Quarterly for Exercise and Sport, 2018)
Purpose: The purpose of this study was to compare the kicking performance of young soccer players in the U9 to U20 age groups. Method: Three hundred and sixty-six Brazilian players were evaluated on an official pitch using three-dimensional kinematics to measure (300 Hz) ball velocity (Vball), foot velocity (Vfoot), Vball/Vfoot ratio, last stride length, and distance between the support foot and the ball. Simultaneously, a two-dimensional procedure was also conducted to compute (60 Hz) the mean radial error, bivariate variable error, and accuracy. Possible age-related differences were assessed through one-way analysis of variance and magnitude-based inferences. Results: Ball velocity increased by 103% (p < .001, Eta2 = .39) from the U11 age group (48.54 ± 8.31 km/hr) to the U20 age group (98.74 ± 16.35 km/hr). Foot velocity presented a 59% increase (p < .001, Eta2 = .32) from the U11 age group (49.08 ± 5.16 km/hr) to U20 (78.24 ± 9.49 km/hr). This finding was due to improvement in the quality of foot-ball impact (Vball/Vfoot ratio) from U11 (0.99 ± 0.13 a.u.) to U20 (1.26 ± 0.11 a.u.; p < .001, Eta2 = .25). Parameters such as mean radial error and accuracy appeared to be impaired during the growth spurt (U13-U15). Last stride length was correlated, low to moderately high, with Vball in all age groups (r = .36-.79). Conclusions: In summary, we concluded that simple biomechanical parameters of kicking performance presented distinct development. These results suggest that different training strategies specific for each age group could be applied. We provide predictive equations to aid coaches in the long-term monitoring process to develop the kick in soccer or search for talented young players.